Triangular conidia of Sphacelia sorghi on grass weed Dicanthium caricosum - P.G. MOGHE, C.S. SANGIT RAO and (Indian Phytopathology, 2002)
The conidial morphology of isolates of S. sorghi [Claviceps sorghi] collected from sorghum and other grass weed hosts was studied. In D. caricosum the conidia were triangular whereas in the other hosts single celled, hyaline macroconidia were observed. Cross-inoculation of the isolates between sorghum and the grass weeds was successful.